2020
DOI: 10.3390/polym12051064
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of Flexible and Semiflexible Chains Confined in Nanoposts Array of Various Geometries

Abstract: The conformation and distribution of a flexible and semiflexible chain confined in an array of nanoposts arranged in parallel way in a square-lattice projection of their cross-section was investigated using coarse-grained molecular dynamics simulations. The geometry of the nanopost array was varied at the constant post diameter dp and the ensuing modifications of the chain conformation were compared with the structural behavior of the chain in the series of nanopost arrays with the constant post separation Sp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(96 reference statements)
1
0
0
Order By: Relevance
“…Recently, Cifra et al have studied the conformation and distribution of flexible and semiflexible polymers in an array of nanoposts, and found that the polymer can be confined in one of the channel-like interstitial volumes between nanoposts or partition among these volumes, depending on the chain stiffness and the crowding effect imposed by nanoposts. [43][44][45][46] This is similar to the distribution behavior of polymer confined in two interconnected cavities. [47][48][49][50] Experimentally, Nykypanchuk et al have studied the partitioning of a single DNA in two interconnected spherical cavities prepared by the colloidal templating method.…”
Section: Introductionsupporting
confidence: 71%
“…Recently, Cifra et al have studied the conformation and distribution of flexible and semiflexible polymers in an array of nanoposts, and found that the polymer can be confined in one of the channel-like interstitial volumes between nanoposts or partition among these volumes, depending on the chain stiffness and the crowding effect imposed by nanoposts. [43][44][45][46] This is similar to the distribution behavior of polymer confined in two interconnected cavities. [47][48][49][50] Experimentally, Nykypanchuk et al have studied the partitioning of a single DNA in two interconnected spherical cavities prepared by the colloidal templating method.…”
Section: Introductionsupporting
confidence: 71%